2005
DOI: 10.1097/01.ede.0000183166.68809.b0
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to Ambient Ozone and Lung Function in Young Adults

Abstract: A history of increased level of lifetime exposure to ambient O3 is associated with decreased function of airways in which O3 deposition in the lungs is the greatest. Adolescents with intrinsically smaller airways appear to be at greatest risk. Any environmental or genetic factors that lead to reduced airway size may lead to increased susceptibility to the adverse effects of ambient ozone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
136
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(143 citation statements)
references
References 42 publications
(37 reference statements)
5
136
1
1
Order By: Relevance
“…Findings of previous studies have shown that prolonged inhalation of O 3 gas damages the respiratory system (6)(7)(8)(9)(10)(11)(12) and extrapulmonary organs (13,14). A series of meta-analyses and evaluation of geographic and seasonal O 3 gas-related risk has provided evidence for the association between O 3 gas and mortality (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Findings of previous studies have shown that prolonged inhalation of O 3 gas damages the respiratory system (6)(7)(8)(9)(10)(11)(12) and extrapulmonary organs (13,14). A series of meta-analyses and evaluation of geographic and seasonal O 3 gas-related risk has provided evidence for the association between O 3 gas and mortality (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, O 3 is well known to have deleterious effects on materials, human health and plants (PORG, 1997). Indeed, O 3 is responsible for damages on polymeric materials such as rubbers, but also on textiles, dyes, surface coatings, metals and buildings materials (Lee et al, 1996;Massey, 1999;Ahmad et al, 2000;Almeida et al, 2000;Boyce et al, 2001) and causes deleterious impacts to human health, including lung inflammation, reduction in lung function, respiratory diseases, and mortality (Rastogi et al, 1991;Uysal and Schapira, 2003;Bell et al, 2005;Ito et al, 2005;Levy et al, 2005;Targer et al, 2005;Hazucha and Lefohn, 2007). On vegetation, O 3 slows-down the stomatal closing, decreases the photosynthetic capacity and alters plant biomass and leaf area, although these effects depend on species, canopy structure and age of tissues (Paoletti, 2005;Paoletti and Grulke, 2005;Ainsworth, 2008;Wittig et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The health effects related to short-term ozone exposure include irritation of eyes and throat, adverse effects on pulmonary function, aggravation of respiratory symptoms, and increase in medication usage, hospital admissions and mortality. The long-term exposure can cause reduction in lung function development [6,7]. Children, adults who are active outdoors [8], and people with preexisting respiratory illnesses are more sensitive to ozone than others.…”
Section: Introductionmentioning
confidence: 99%